Discursos sobre o livro infantil (1968 1978) - Almeida, Licia Maria Pedreira de (2009)
The purpose of this study is to present the discourses about children's book in the period of 1968 to 1978. The speeches are divided into two parts, for the purpose of research: the first one is related to the official educational legislation passed by federal and paulistas agencies. The second one instance refers about two places: the National Foundation of Youth and Children's Book - FNLIJ, inaugurated in 1968 and the children s library of the São Paulo city, Biblioteca Infantil Monteiro Lobato. The sources used are, in addition to legal acts, ordinances and resolutions, the curriculum guides for teaching, the Newsletters of FNLIJ and Bibliographies of Children s Literature produced by Biblioteca Infantil Monteiro Lobato. The documents show the search criteria and the choice of titles and authors of books prescribed for teachers use in classrooms. Pointing in the same way, the representations about the act of reading of cultural mediators, who often interfered in the production of children's book adapting it to new requirements. Among the representations examined, are found in the homogeneous speaches the fomentation of the habit of reading in schools and libraries. Following these speeches, it is found, with children's literature of the 1970s, the disclosure of pleasure and love of reading done by agents circulating in the scenarios that involved books and reading. The research falls in the field of education history that addresses the formation of school "form". Based on the work of Anne-Marie Chartier and Jean Hébrard, which has the intention to reveal the discourses about reading, this essay, included as part of cultural history, will discuss the representation of social actors involved in the teaching of reading and selection of books for paulista s schools